2022
DOI: 10.3389/fmicb.2022.855961
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanism of the β-Lactamase Mediated β-Lactam Antibiotic Resistance of Pseudomonas aeruginosa Isolated From a Chinese Teaching Hospital

Abstract: Pseudomonas aeruginosa can cause infections in the blood, lungs (pneumonia), or other parts of the body after surgery. To investigate the molecular characteristics of β-lactam antibiotic resistance of P. aeruginosa isolated from a hospital population between 2015 and 2017, in this study, the antimicrobial susceptibility and the resistance gene profile of the bacteria were determined. The Pulsed-field gel electrophoresis (PFGE) was used to characterize the clonal relatedness and sequencing and comparative genom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 33 publications
1
5
2
Order By: Relevance
“…The presence of bla TEM in K.pneumoniae isolates is in agreement with (65) they reported in a study conducted in Iran that bla TEM in K.pneumoniae isolates was about (12.4%), (66) reported the prevalence rates for bla TEM (12.35%), in urinary K. pneumonia strains ; (67)revealed that 16.1% of K.pneumoniae isolates produced bla TEM while higher percentage than our finding recorded by (68) about 83% . P.aeruginosae in our study produced bla TEM gene in accordance with a study conducted by (69) they reported that 15% of P.aeruginosae isolates were carry bla TEM gene ; (70) investigated that 26.7% of P.aeruginosae strains were have bla TEM ; (71) , revealed that 27.72% of P.aeruginosae isolates were harbored bla TEM gene ; while in a study conducted in Chinese teaching hospitals , (72) reported that very low percentage 4.5% of P.aeruginosae expressed bla TEM gene .…”
Section: Discussionsupporting
confidence: 87%
“…The presence of bla TEM in K.pneumoniae isolates is in agreement with (65) they reported in a study conducted in Iran that bla TEM in K.pneumoniae isolates was about (12.4%), (66) reported the prevalence rates for bla TEM (12.35%), in urinary K. pneumonia strains ; (67)revealed that 16.1% of K.pneumoniae isolates produced bla TEM while higher percentage than our finding recorded by (68) about 83% . P.aeruginosae in our study produced bla TEM gene in accordance with a study conducted by (69) they reported that 15% of P.aeruginosae isolates were carry bla TEM gene ; (70) investigated that 26.7% of P.aeruginosae strains were have bla TEM ; (71) , revealed that 27.72% of P.aeruginosae isolates were harbored bla TEM gene ; while in a study conducted in Chinese teaching hospitals , (72) reported that very low percentage 4.5% of P.aeruginosae expressed bla TEM gene .…”
Section: Discussionsupporting
confidence: 87%
“…We report that bla CTX-M-15 is the predominant ESBL encoding gene present in P. aeruginosa and is highly disseminated in the reported '23' STs. Similar resistance encoding genes were reported globally including in China, but our study is in contrast with some reports in China [32,33,34,35]. No bla OXA-48 gene was reported in this study.…”
Section: Plasmid Analysiscontrasting
confidence: 56%
“…We have recorded high resistance for commonly used antimicrobials piperacillin-tazobactam (56%), cefepime (40%), ceftazidime (39%), imipenem (36%) and cipro oxacin (32%) respectively. P. aeruginosa strains show a similar resistance phenotype globally and in other provinces of China such as Zhejiang and rates of resistance are increasing rapidly which is particularly alarming in the healthcare sector [31,32]. In addition to this 42% ESBL producers were observed by VITEK ® 2 compact system (BioMerieux, France) and DDDM which is lower compared to Chinese data but is similar to other Asian countries such as Malaysia [33,34].…”
Section: Plasmid Analysismentioning
confidence: 76%
“…Genes are color-coded according to the following key: dark blue, transposase and integrase genes; red, antimicrobial resistance genes; dark red, mercury resistance genes; grey, tra gene complex; dark green, DNA metabolism; brown, plasmid maintenance and replication; white, all other genes the bla CARB-2 gene presented a different resistance profile from the other two, which included reduced susceptibility to ceftazidime, cefepime, aztreonam and piperacillintazobactam. Conjugation experiments performed on E. coli by Lin et al demonstrated that carriage of the closely related bla CARB-3 gene was associated with reduced susceptibility to piperacillin-tazobactam, ceftazidime, and cefepime [15]. The additional resistance genes found among our isolates were located in gene cassettes within class 1 integrons, demonstrating that C. freundii can acquire resistance genes from other organisms.…”
Section: Discussionmentioning
confidence: 52%